Clinical Pathobiochemistry of Vitamin B12 Deficiency: Improving Our Understanding by Exploring Novel Mechanisms with a Focus on Diabetic Neuropathy - Schleicher, Erwin; Didangelos, Triantafyllos; Kotzakioulafi, Evangelia; Cegan, Alexander; Peter, Andreas; Kantartzis, Konstantinos (Nutrients, 2023)
Vitamin B12 (B12) is an essential cofactor of two important biochemical pathways, the degradation of methylmalonic acid and the synthesis of methionine from homocysteine. Methionine is an important donor of methyl groups for numerous biochemical reactions, including DNA synthesis and gene regulation. Besides hematological abnormalities (megaloblastic anemia or even pancytopenia), a deficiency in B12 may cause neurological symptoms, including symptoms resembling diabetic neuropathy. Although extensively studied, the underlining molecular mechanism for the development of diabetic peripheral neuropathy (DPN) is still unclear. Most studies have found a contribution of oxidative stress in the development of DPN. Detailed immunohistochemical investigations in sural nerve biopsies obtained from diabetic patients with DPN point to an activation of inflammatory pathways induced via elevated advanced glycation end products (AGE), ultimately resulting in increased oxidative stress. Similar results have been found in patients with B12 deficiency, indicating that the observed neural changes in patients with DPN might be caused by cellular B12 deficiency. Since novel results show that B12 exerts intrinsic antioxidative activity in vitro and in vivo, B12 may act as an intracellular, particularly as an intramitochondrial, antioxidant, independent from its classical, well-known cofactor function. These novel findings may provide a rationale for the use of B12 for the treatment of DPN, even in subclinical early states.
Keywords: Vitamin B 12; redox; Diabetic Neuropathies; Humans; oxidative stress; homocysteine; Vitamins; vitaminy; vitamin B 12; cobalamin; lidé; Antioxidants; laboratory biomarker; methylmalonic acid; peripheral neuropathy; Diabetes Mellitus; antioxidancia; nedostatek vitaminu B12; Vitamin B 12 Deficiency; reactive oxygen species; diabetes; methionin; Methionine; Vitamin B12; diabetes mellitus; diabetické neuropatie